O impacto da arrecadação do Imposto de Renda Retido na Fonte sobre a economia local: uma análise das capitais brasileiras de 2018 a 2022 - Sousa, Clarice Cynara de (2024)
Considering the high financial dependence of municipalities in relation to transfers of resources from the States and the Union, this work seeks to evaluate the impacts of Income Tax Withheld at Source on the local economy based on a panel analysis for the 26 capitals between 2018 and 2022. The hypotheses underlying the study arise from the proposition that greater autonomy, provided in one of its ways by the withholding of income tax from civil servants and public service providers, can enable greater investment or, in other words, In a similar way, provide more payment capacity due to the payment of pre-existing debt service. Thus, the relationship between a measure of autonomy via IRRF and investments and capital expenditures in Brazilian capitals in the subsequent year is investigated. The representation of IRRF revenue in local tax revenue is the measure of autonomy generated by the IRRF, while, alternatively, the volume of income tax withheld in real terms is a proxy for economic size. As a result, fixed effects models allow us to verify that there is a positive relationship between the representation of IRRF in tax revenue and the investments made, as well as in relation to public debt service, in the subsequent period. On the other hand, a greater volume of IRRF collected in real terms implies a drop in investments or future capital expenditure. Taken together, these results suggest alternative sources of investment, or capital expenditure, for larger economies.